Aktywność zawodowa i bezrobocie ludności mieszkającej na wsi - Hybel, Jan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1996)
An analysis of rural unemployment is presented here. Population and people unemployed are divided by sex, age, educational level and region. The given data are for rural population and those unemployed registered by local Labour Office and Main Statistical Office. The collected data are for the years 1988-1994. Problems presented here concern: 1) Characteristics of active rural population, unemployment of people on rural areas, 2) Unemployment rate in Poland and differentiation according to the regions, 3) Methods of reducing rural unemployment. The analysis allows for following conclusions: * Rural unemployment rate is only 2.5% lower than in urban areas, * Rural unemployment concerns mostly young people, less educated and looking for the job for 12 months and longer.